Inter(Multi, Trans)disciplinarity - Achieving Synergy - Žic Fuchs, Milena (2011)
The notions of Inter(Multi, Trans)disciplinarity and Monodisciplinarity in Personalised Medicine are discussed. These notions are of essential importance because Personalised Medicine goes well beyond medical issues. An interdisciplinary approach to any subject implies new ways of interpreting and integrating them into wider networks of knowledge. "Innovative knowledge" helps bridge the gap between the so-called hard and soft sciences and at the same time provides the necessary link to society. New "cultures of knowledge" growing out of interdisciplinary research can be seen as one of the most innovative facets of future research.